Herbal Formula Extract Ameliorates Anxiety and Cognitive Impairment via Regulation of the Reelin/Dab-1 Pathway in a Murine Model of Post-Traumatic Stress Disorder - Hee Ra Park; Mudan Cai; Eun Jin Yang (MDPI AG, 2024)
We investigated the effects of epigenetic modifications on post-traumatic stress disorder (PTSD) using a novel combination of herbal medicines from Panax ginseng, Astragalus membranaceus, Atractylodes macrocephala, and Glycyrrhiza uralensis. The herbal formula extract (HFE) (250 mg/kg) was administered orally once daily for 14 days to determine its effects on PTSD in mice by combining prolonged stress and foot shock. The open field and Y-maze tests determined the effect of HFE on PTSD-induced anxiety and cognition. Hippocampal neuronal plastic changes and molecular mechanism were verified. Treatment with HFE decreased anxiety-like behavior and enhanced cognition. Moreover, it reduced the number of PTSD-related hilar ectopic granule cells in the dentate gyrus (DG). PTSD mice showed reduced neuronal plasticity of doublecortin+ cells in the DG, which was restored by HFE treatment. HFE reversed PTSD-induced inhibition of the Reelin/Dab1 pathway, a critical signaling cascade involved in brain development, and regulated Reelin methylation. Furthermore, DNA methylation, methyl-CpG binding protein 2, and DNA methyltransferase 1, which were elevated in the hippocampus of PTSD mice, were restored following HFE treatment. HFE increased the expression of synaptic plasticity-related factors in the hippocampus of PTSD mice. Our findings suggest that HFE can facilitate PTSD treatment by alleviating behavioral abnormalities through the restoration of hippocampal dysfunction via regulation of the Reelin/Dab-1 pathway and DNA methylation in the hippocampus.